2018
DOI: 10.29328/journal.jpsp.1001022
|View full text |Cite
|
Sign up to set email alerts
|

Advances in research of the structural gene characteristics of the aflatoxin biosynthetic gene cluster

Abstract: Afl atoxins, produced by Aspergillus spp., are strongly toxic and carcinogenic fungal secondary metabolites. Afl atoxin biosynthesis is a complex process and involves at least 30 genes clustered within an approximately 75 kB gene cluster. In this paper, we reviewed current status of the researches on the characterized structural genes involved in afl atoxin biosynthesis and their roles in afl atoxin-producing fungi, especially in A. fl avus and A. parasiticus, which will improve our understanding of the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 98 publications
(249 reference statements)
0
2
0
Order By: Relevance
“…The aflatoxin biosynthesis pathway requires at least 18 enzymatic reactions and involves up to 30 genes ( 40 ). AflO , encoding O -methyltransferase I, is a key enzyme in aflatoxin biosynthesis ( 41 ), and studies have found that loss of aflO can significantly inhibit aflatoxin production ( 42 ). The aflU gene is located at the end of a gene cluster and encodes a polypeptide with a heme-binding domain of cytochrome P450 monooxygenase, involved in aflatoxin biosynthesis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aflatoxin biosynthesis pathway requires at least 18 enzymatic reactions and involves up to 30 genes ( 40 ). AflO , encoding O -methyltransferase I, is a key enzyme in aflatoxin biosynthesis ( 41 ), and studies have found that loss of aflO can significantly inhibit aflatoxin production ( 42 ). The aflU gene is located at the end of a gene cluster and encodes a polypeptide with a heme-binding domain of cytochrome P450 monooxygenase, involved in aflatoxin biosynthesis ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“… A schematic diagram of the biosynthesis pathway of aflatoxin B1, indicating the corresponding encoding genes. Modified from [ 47 ]. …”
Section: Figurementioning
confidence: 99%